Implementation of The Learning Media "Lectora Inspire" to Raise The Activity of Class Three Intensive Students of Darussalam Gontor Islamic Boarding School for Girls Campus 2 and their Learning value in al-Balāgoh - Yoke Suryadarma; Nabila Nabila (Educan : Jurnal Pendidikan Islam, 2020)
Al-Balāgoh is an Arabic subject that aims to improve proficiency in Arabic language students. Darussalam Gontor Islamic Boarding School for Girls Campus 2 pays great attention to this subject and strives to make this subject interesting to female students. Therefore, the researcher tried to come up with a research for teaching al-Balāgoh using the "Lectora Inspire" as learning media. The researcher wanted to achieve the effectiveness of this learning media to raise the activity of Class Three Intensive Students in al-Balāgoh and their results for the academic year 1440-1441. This research is a Classroom Action Research method that is conducted in four successive steps to achieve the purpose goals. The results of this research showed that teaching al-Balāgoh using the learning media "Lectora Inspire" raised the activity of female students' learning in al-Balāgoh by achieving 43% in the first session, and then increasing of 82% in the second session, and although raised the learning result by achieving 23% in the first session, and an increase of 82% in the second session. Hence, teaching al-Balāgoh using the "Lectora Inspire" learning media can be used in another subject to increase student learning activity and their results.